Teaching poverty and health: importing transformative learning into the structures and paradigms of medical education - Cartmill, Carrie; Whitehead, Cynthia; Ihekwoaba, Esther; Goel, Ritika; Green, Samantha; Haidar, Mona; Harriott, Dawnmarie; Wright, Sarah (Canadian Medical Education Journal, 2021)
Background: As a paradigm of education that emphasizes equity and social justice, transformative education aims to improve societal structures by inspiring learners to become agents of social change. In an attempt to contribute to transformative education, the University of Toronto MD program implemented a workshop on poverty and health that included tutors with lived experience of poverty. This research aimed to examine how tutors, as members of a group that faces structural oppression, understood their participation in the workshop. Methods: This research drew on qualitative case study methodology and interview data, using the concept of transformative education to direct data analysis and interpretation. Results: Our findings centred around two broad themes: misalignments between transformative learning and the structures of medical education; and unintended consequences of transformative education within the dominant paradigms of medical education. These misalignments and unintended consequences provided insight into how courses operating within the structures, hierarchies and paradigms of medical education may be limited in their potential to contribute to transformative education. Conclusions: To be truly transformative, medical education must be willing to try to modify structures that reinforce oppression rather than integrating marginalized persons into educational processes that maintain social inequity.